Multidomain Cognitive Impairment in Children With Pseudotumor Cerebri Syndrome. Issue 1 (4th March 2022) - Mahajnah, Muhammad; Suchi, Ariel T.; Zahakah, Hazar; Sharkia, Rajech; Shuhaiber, Shaden R.; Srugo, Isaac; Genizi, Jacob
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Although prompt and suitable treatment of pseudotumor cerebri syndrome (PTCS) leads to an excellent prognosis and can prevent optic nerve atrophy, adults show long-lasting neurocognitive deficits even with prompt treatment. The purpose of our study was to evaluate cognitive outcomes in pediatric patients with PTCS. Methods: We performed a prospective study on children diagnosed with PTCS and a healthy control group. Children with pre-existing neurological conditions or psychiatric drug use were excluded. Both groups underwent a neurocognitive evaluation, using the NeuroTrax computerized battery of tests. The PTCS group were tested 3 months after the initial diagnosis. Results: We evaluated 82 children (49 females [60%], 6.5–16 years old, mean age 13.3), including 26 diagnosed with idiopathic PTC and 56 controls. Global cognitive score ( P < 0.001), verbal memory ( P < 0.001), executive function ( P < 0.001), attention ( P < 0.003), and information processing speed ( P < 0.004) were all significantly lower in the PTCS group. No differences were found between children currently being treated and those whose symptoms had resolved and treatment was stopped. Conclusions: Children with PTCS experience comprehensive cognitive decline that persists after the resolution of the symptoms and treatment.